1999
DOI: 10.1038/sj.leu.2401361
|View full text |Cite
|
Sign up to set email alerts
|

Role of MRP1 in multidrug resistance in acute myeloid leukemia

Abstract: The best characterized resistance mechanism in adult acute myeloid leukemia (AML) is the one mediated by the MDR1 gene which has been shown to be associated with poor outcome. However, alternative proteins such as the more recently recognized multidrug-associated protein (MRP1), may also contribute to the resistance to anthracyclines and etoposide in AML. Recently, the role of this protein was discussed and was unclear in AML. However, recent data concerning the functionality and the modulation of the activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 28 publications
1
25
0
2
Order By: Relevance
“…Apoptosis is an energy requiring suicide programme, which is normally activated in response to cellular damage, or following physiological signals such as death receptor ligation or withdrawal of survival signals. 1,2 Previously studied mechanisms employed by a variety of cells to export or neutralise anti-neoplastic drugs, include p-glycoprotein, 3 the multi-drug resistance-associated protein, 4 and glutathione S-transferases. 5 By effectively reducing the intracellular concentration of drugs, these mechanisms increase cellular tolerance and suppress the normal apoptotic response.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is an energy requiring suicide programme, which is normally activated in response to cellular damage, or following physiological signals such as death receptor ligation or withdrawal of survival signals. 1,2 Previously studied mechanisms employed by a variety of cells to export or neutralise anti-neoplastic drugs, include p-glycoprotein, 3 the multi-drug resistance-associated protein, 4 and glutathione S-transferases. 5 By effectively reducing the intracellular concentration of drugs, these mechanisms increase cellular tolerance and suppress the normal apoptotic response.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] In cell lines, we have found that JC-1 was not a substrate of MRP1 (unpublished data, 2000), as were Rh123 and calcein-AM.…”
Section: Discussionmentioning
confidence: 99%
“…Multidrug resistant-related protein 1 (MRP1), another transporter protein, is sometimes expressed in AML [58]. However, the clinical importance of MRP1 is relatively limited among the mechanisms of resistance to GO [59].…”
Section: Drug Resistancementioning
confidence: 99%